SOME NEW PEROVSKITE-RELATED COMPOUNDS IN THE BAO-TL2O3 SYSTEM - Zhou, W; Liu, R; Edwards, P (1991)
Two new perovskite-related phases in the Tl2O3BaO system have been synthesized and investigated by X-ray powder diffraction and high resolution electron microscopy. A solid solution phase exists with the compositions between BaTl2O4 and Ba4Tl10O19. The typical composition, Ba6Tl14O27, has an orthorhombic unit cell with a = 17.724, b = 6.890, and c = 10.235 Å. The compound Ba2Tl10O17 has a 1 × 3.5 × 1 superstructure derived from the Ba6Tl14O27 phase, being also orthorhombic with unit cell dimensions of a = 17.676, b = 24.167, and c = 10.110 Å. The relationships between both these new structures, the recently discovered Ba4Tl6O13 and the perovskite-like basic structures, are discussed. © 1991.